Investigator’s gender and clinical trials performance in recruitment of patients - Milovanov, Svyatoslav (International Journal of Clinical Trials, 2023)
Mostly of attraction to gender is related with participant subjects of clinical trials. Based on percentage of subject of each gender it is calculating enrollment fracture, bias and some other indexes. Enrollment is very important parameter and genders is considering as one of the internal factors which is influencing to enrollment. Authors also marking the more prevalence of male above the female in some aspects of clinical trials. It is obviously that investigators also has a differences in gender and this could have a differences in some parameters and enrollment is one of them. Enrolment parameters also not developed very much. We stepped forward to find out the relations of gender’s investigator and the enrollment. Materials and methods: Data of four clinical trials II-III phases in oncology and hematology, conducted since 2007 to 2017 years has been used for retrospective analysis. Study objectives: to investigate the study recruitment rate using different parameters and it’s changes along with acting of gender’s of investigator; to develop new parameters and values (derivatives) which could be sensitive for evaluation of enrollment. Statistical analysis: data had been collected from feasibility questionnaires, open statistical sources. Results: It was showed the values of enrollment parameters in perspective of investigator’s gender. Discussion: Statistical differences in some existing and developed enrollment parameters has been found. Gender’s influence to enrollment also was investigated.